STUDY OF POLLUTANT DISTRIBUTION IN BENOA BAY USING NUMERICAL SIMULATION AND SATELLITE DATA - Ardana, Komang; Mahendra, M S (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 2)
Euthrofication that caused by nitrate and phosphate contamination and also sedimentation process is the mainproblem that took place in Benoa Bay Territorial water. The distribution of phosphate pollutant in Benoa bay territorialwater was modeled by numeric of Princeton Ocean model (POM). The input of this pollutant model were a tidal currentpattern, M2 tidal current residue, biological factor, physic and chemistry, that influenced pollutant concentration.Meanwhile, the sedimentation concentration was mapped with ALOS AVNIR-2 sensor image satellite and this image wasanalysed with statistic method (Linear Regression).The result of phosphate modeling concentration was 0.1 mg/1 to 0.0022 mg/1, where the concentration wascategorized very hazardous to the territorial water environment. Because the phosphate concentration in a pollutantresources was beyond the standard level of environmental quality, that was 0.015 mg/1 for fishery cultivation and alsotourism activity (Bali Governor Regulation No.8th 2007). While, the direction of the distribution was affected by currentpattern of movement, that was when the ebb level of high water moving into the bay and when the ebb to high tidemoving out of the bay.The result of statistic approaches with ALOS of AVNIR-2 censor can be used for mapping sedimentationdistribution advantages in Benoa Bay. The values were: R2 Band 1 is 0.3839, Band 2 is 0.6123 and Band 3 is 0.5468. Inthis methodology, the correlation was not significant, due to, the quantity of in-situ data was small and the time researchwas not at the same time with satellite data.
Keywords: Tidal Current, M2 Residual, Phosphate pollutant and satellite image.